2D Materials and Primary Human Dendritic Cells: A Comparative Cytotoxicity Study. Issue 20 (21st April 2022) - Lin, Hazel; Peng, Shiyuan; Guo, Shi; Ma, Baojin; Lucherelli, Matteo Andrea; Royer, Cathy; Ippolito, Stefano; Samorì, Paolo; Bianco, Alberto
Abstract: Human health can be affected by materials indirectly through exposure to the environment or directly through close contact and uptake. With the ever‐growing use of 2D materials in many applications such as electronics, medical therapeutics, molecular sensing, and energy storage, it has become more pertinent to investigate their impact on the immune system. Dendritic cells (DCs) are highly important, considering their role as the main link between the innate and the adaptive immune system. By using primary human DCs, it is shown that hexagonal boron nitride (hBN), graphene oxide (GO) and molybdenum disulphide have minimal effects on viability. In particular, it is evidenced that hBN and GO increase DC maturation, while GO leads to the release of reactive oxygen species and pro‐inflammatory cytokines. hBN and MoS2 increase T cell proliferation with and without the presence of DCs. hBN in particular does not show any sign of downstream T cell polarization. The study allows ranking of the three materials in terms of inherent toxicity, providing the following trend: GO > hBN ≈ MoS2, with GO the most cytotoxic. Abstract : 2D materials hexagonal boron nitride (hBN), graphene oxide (GO) and MoS2 are taken up by primary human dendritic cells (DC) without affecting their viability. hBN and GO increase DC maturation, while GO increases release of reactive oxygen species and pro‐inflammatory cytokines. hBN and MoS2 increase T cell proliferation. The overall cytotoxicity follows this trend: GO > hBN ≈ MoS2 .